The relevance of the new PA in Philippine public administration - Pilar, Nestor N. (1982)
The relevance of New PA may be assessed at two levels, the conceptual and the technical. Conceptually, New PA appears to be compatible with the development goals and aspirations of the country. Rather than promote only efficiency, economy and effectiveness, New PA seeks to change administrative structures and processes to advance also relevance, social equity and client welfare. At the technical level, many of the administrative methods, tools and techniques in current use find their roots in New PA. The search for alternatives to bureaucracy, e.g., the IAD approach, analytic tools like cost-benefit analysis, and sensitizing techniques like OD comprise a response of administrative technology to the demand of the day - producing an administrator who is managerially effective, committed and sensitive to others' needs.
Keywords: Public administration; Bureaucracy